Embryonic Deaths in the Sahiwal Friesian Cows in an Institutional Farm in Malaysia - Hj. Rusli, Roslaini (1998)

(untitled)
Reproductive wastage is a major cause of production loss in dairy animals. Fertilization failure and embryonic death are suggested to be the main causes of reproductive loss. The dairy industry in Malaysia is hampered by poor reproductive performance which is manifested by repeat breeding and lengthened calving interval. Whether this is due to fertilization failure or embryonic death has never been determined. This study is belief to be the first in the tropics in trying to quantify reasons for reproductive inefficiency in crossbred cows in the tropical environment and attempts to relates the influence of the hot ambient tropical temperature and humidity to embryonic mortality. In this study reproductive inefficiency is caused by fertilization failure (9%), luteal insufficiency at insemination (10%), embryonic mortality (53%) and foetal deaths (8%). Embryonic mortality is the major caused of reproductive inefficiency. BED contributed to 73% of all embryonic mortalities with 62% of these taking place from Day 8-21 of the gestation period. Fertilization rate of 81% is achievable in the tropics. Treatment with exogenous progesterone do not increased pregnancy rate neither does keeping early pregnant animal under stallfeeding, but both factors had a positive association in contributing to embryonic mortality. Poor reproductive performance in this study in not due to fertilization failure but due to embryonic mortality. This study has challenged the traditionally accepted reason of poor heat detection being the main reason for poor reproductive performance (due to fertilization failure) in the Sahiwal Friesian cows.